The mechanical model and refinement mechanisms of graphite particle of nodular cast iron during the friction stir processing. (29th November 2019) - Tang, Jingming; Shen, Yifu; Yao, Xin
Abstract: The nodular cast iron was surface modified by friction stir processing (FSP). The morphology and distribution of the graphite particles in the processed zone were observed. The torque, axial force and traverse force applied to the tool during the FSP were measured. The forces applied to the graphite particles at different locations in the processed zone were analyzed. Based on analysis of the above experimental results, the mechanical model of graphite particle was established, and the mechanisms of fragmentation and refinement of graphite particles were discussed in detail. The effect of refining and distributing of the graphite particles was optimum when the rotational speed and traverse speed of the tool were 1100 rpm and 80 mm min −1, respectively. The graphite particles, which were in direct contact with the tool, were subjected to the extrusion pressure, friction, thrust, resistance and the torque applied by the tool and the plastic material, and the forces and the torque were large. However, the forces and the torque were small when the graphite particle were not in direct contact with the tool. The extrusion pressures, frictions, thrusts and torque applied to the graphite particles resulted in deformation of extrusion, shear and torsion of the graphite particles. There were mainly four types of refinement mechanisms of the graphite particles in the stir zone (SZ) and three types of refinement mechanisms in the thermo-mechanically affected zone (TMAZ).